Mining Management by Nahdlatul Ulama and Muhammadiyah: Beyond Politics and People’s Welfare - Mustapa, Hasan; Ansori, Faruq; Hermawan, Endang; Syi’aruddin, M. Anwar; Fauziah, Alya (Candidate: Jurnal Sains Politik, 2025)
The Muhammadiyah community experienced considerable surprise when its central leadership agreed to the government's proposal for managing mining operations in July 2024. In contrast to Nahdlatul Ulama, which has established a robust history of cooperative engagement with governmental authorities, Muhammadiyah is predominantly recognized for its focus on community welfare initiatives. Despite extensive research on mining governance and corporate social responsibility, there remains a significant gap in understanding how religious mass organizations, particularly those without prior mining experience, navigate the complex interplay between political incentives and welfare objectives when entering extractive industries. This study addresses this gap by examining the socio-political dynamics and organizational capacity of NU and Muhammadiyah in accepting mining concessions from the Joko Widodo administration. Employing qualitative methodology, this research collected primary data through document analysis of official statements, organizational decrees, news reports, and government regulations from both organizations. Data were analyzed using a political development framework, focusing on three dimensions: development actors, power relations, and ideological foundations. The findings reveal that NU's acceptance of mining concessions is significantly shaped by its political orientation and historical pattern of cooperative politics with the government, driven primarily by financial pressures to sustain its extensive network of educational and social institutions. Conversely, Muhammadiyah's decision reflects a more deliberative process grounded in theological justification and legal analysis, supported by its stronger socio-economic resource base from philanthropic business activities. However, both organizations demonstrate limited capacity in managing high-risk sectors such as mining and mineral extraction, lacking technical expertise and operational experience in the extractive industry. This study contributes novel insights into how religious civil society organizations negotiate their autonomy and critical function when co-opted into state-led economic initiatives.